Pembuatan Aplikasi Kamus Istilah Dunia Bisnis Berbasis Android - Djohan, Timotius Revelano Saliby; Andjarwirawan, Justinus; Santosa, Teguh (Jurnal Infra, 2018)
In today's world where globalization is very heavy and unstoppable, many young people today plunge into the business world. With so many words uptake and terms in the business world, then developed an application that can help ease in learning the term business world. In this thesis is done making the application to utilize Levenshtein Distance Algorithm and Wildcard as supporting media of information, so user easier in looking for a word. This app will run on android devices.